English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-20 15:02:29 · 6 answers · asked by steph158_4 1 in Science & Mathematics Mathematics

6 answers

mx + 3 = 4 - nx
mx + nx = 4 - 3
x(m + n) = 1
x = 1 / (m + n)
><

2007-01-21 03:22:08 · answer #1 · answered by aeiou 7 · 5 0

mx + 3 - 3 + nx = 4 - nx - 3 + nx

mx + nx = 1

x(m + n) = 1

x = 1/(m + n)

2007-01-20 15:15:05 · answer #2 · answered by Jim Burnell 6 · 1 0

mx + 3 = 4 - nx
mx+nx=1
x(m+n)=1
x= 1/(m+n)

2007-01-20 15:14:22 · answer #3 · answered by      7 · 1 0

mx + 3 = 4 - nx

Divide each side by x

mx/x + 3/x = 4/x -nx/x (Simplify)

m + 3/x = 4/x -n (subtract 3/x from each side)
m= 1/x -n (solve for x by inversion)
1/m= x - 1/n (add 1/n to each side)
1/m + 1/n = x
x= 1/m+n

Best guess...

2007-01-20 15:18:28 · answer #4 · answered by RHJ Cortez 4 · 1 0

Subtract 3 from both sides:
mx=1-nx

Add nx from both sides:
mx+nx=1

Factor out an x:
x(m+n)=1

Divide (m+n) from both sides:
x=1/(m+n)

2007-01-20 19:05:00 · answer #5 · answered by Anonymous · 0 0

mx+nx=4-3
x(m+n)=1
x=1\(m+n)

2007-01-20 15:14:40 · answer #6 · answered by Anonymous · 1 0

fedest.com, questions and answers